Синергія впливу лідерських компетенцій та навичок ведення переговорів на ефективність проєктного менеджменту - ZRYBNIEVA, IRYNA; Zavolichna, Tatyana; Zavolichna, Tatyana (Науковий вісник Чернівецького університету, 2021)
The article examines the issues of leadership competencies and negotiation skills of managers in project management processes. The analysis of behavioral models of leaders-managers in the context of influence on productivity of cooperation with stakeholders and formation of an effective team is carried out. The authors identify the features of project management in the sectors of their implementation - business, public / municipal administration and community service. Semantic and contextual analysis of scientific sources indexed in leading databases SCOPUS, WEB of Science, CEEAS (Central & Eastern European Academic Source) was used to determine the degree of research on the impact of leadership competencies and negotiation skills on the effectiveness of project management in medicine. It is substantiated that an important feature of the synergy of leadership competencies and negotiation skills and their impact on project performance is that these competencies become an integral part of the organization's management in both private and public institutions. A successful project manager must be able to manage relationships to interact with both external stakeholders and within the organization. The leader must be a competent negotiator who is open to finding and expanding opportunities and solutions to meet the interests of the parties involved, increasing the value of cooperation between partners in the long run. The analysis of the implementation of cross-border cooperation projects in the field of medicine showed that the leadership style and competence of the manager has a direct and measurable impact on the results of the organization, there is also an indirect impact on clinical practice. A reflective approach to project management serves as a positive model for the entire project team to follow. Heads of health care institutions must be able and responsible for implementing changes in the reform process and accept that the leadership and professional competencies of the leader are the foundation for further success and implementation of health care reform. Mastering negotiation skills will allow managers to better adapt to change, minimize risks and make progress in project management.
Synergy of influence of leadership competences and negotiation skills on the project management effectiveness
Keywords: leadership, manager-leader, leadership competencies, soft skills, negotiation, negotiation skills, project management, medicine, medical field